Application of response surface methodology in modeling and optimization of ceftriaxone decomposition with activated persulfate through zero valence zinc nanoparticles/ultrasonic waves - Zohreh Berizi; Mohammad Reza Zare; Leila rezaei; Ali Parvizimehr; salehe salehnia; Mohsen Rezaei; Nezamaddin Mengelizadeh (Muhandisī-i Bihdāsht-i Muḥīṭ)
Background: The poor degradability of antibiotics in conventional wastewater treatment processes has recently encouraged researchers to use advanced oxidation processes based on persulfate (PS) activation. Therefore, the aim of our study was to remove ceftriaxone through the activation of persulfate with zero valence zinc/ultrasonic waves (Zn0/US). Methods: In this laboratory study, the sample containing the antibiotic ceftriaxone was subjected to persulfate activation through an ultrasonic probe with a frequency of 40 kHz. Optimization of operational parameters such as initial pH, catalyst dose, initial ceftriaxone concentration, reaction time and persulfate concentration was done through response surface methodology (RSM). In optimal conditions, synergistic effect, changes in wavelength scanning, mineralization rate and radical scavenger effect were studied. Finally, ceftriaxone concentration, chemical oxygen demand (COD) and total organic carbon (TOC) were measured through diagnostic devices. Results: Based on RSM analysis of variance, the maximum removal of antibiotic (94.54%), COD (66%) and TOC (54%) in laboratory conditions including pH equal to 3, 0.75 mg/L persulfate and catalyst concentration, 15 mg/L ceftriaxone and 45 minutes of reaction time were obtained. The presence of tert-butyl alcohol and ethanol as scavengers of hydroxyl and sulfate radicals decreased the efficiency rate of the process to 79% and 45% in the reaction time of 45 minutes and emphasized that the active species participate in ceftriaxone degradation. Conclusion: Based on the results, the process of Zn0/US/PS can be considered as a pretreatment process for the effective removal of ceftriaxone from water environments.